KAJIAN FEKUNDITAS DAN DAYA TETAS TELUR IKAN BETUTU (Oxyeleotris marmorata) PADA WAD AH PEMIJAHAN YANG BERBEDA - Sri Karyaningsih (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Assessment of fecundity and hatching rate of betutu fish - sand goby Oxyeleotris marmorata) eggs has been done at the station rearing center in Ngrajek, Magelang Regency, Central Java. The fecundity and hatching rate of sand goby eggs can be used as measuring rod of fry. The result showed that the fecundity of rearing in fiber pond between 4.700 to 10.250 eggs with the hatching rate are 41.44% to 85.06%. The rearing in concrete pond between 5.400 tol4.000 eggs with the hatching rate are 43.20% to 90.00%. Statistical test on relationship indicates that no significant for fecundity and hatching rate about the rearing on different case. The relationship between the fecundity with the body length and the body weight is significant. The fecundity and hatching rate was under the influence of ovary weight, diet and hatchery environment.",